Neuroeffector Mechanisms Involved in the Regulation of Dog Splenic Arterial Tone - Shigetoshi Chiba; Xiao-Ping Yang (Elsevier, 2003)
It has been recognized that sympathetic neurons release several transmitters but mainly adenosine 5'-triphosphate (ATP), noradrenaline, and neuropeptide Y (NPY). Recently, we reported that periarterial nerve electrical stimulation (PNS) produced biphasic vasoconstrictions consisting of an initial transient, predominantly P2X-purinoceptor-mediated constriction followed by a prolonged, α1-adrenoceptor-mediated one in canine isolated splenic arteries. In this article, we tried to analyze the effects of several selective key drugs that influence the PNS-induced responses, and we functionally showed sympathetic transmitter releasing mechanisms by pharmacological analysis using purinergic, adrenergic, and NPYergic agonists and antagonists.